ANALISIS POTENSI DAN PENERIMAAN PAJAK HOTEL DI KOTA PONTIANAK - EDY PURWANTO, B61112052 (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT Taxes as a source of district revenue (PAD) in Pontianak during the periods 2009 to 2013 had not provided optimal results, in which the contribution to the revenue was by an average of 6,95% per  year. Although the realization obtained always exceeded the target with figures above 100%, but if it is associated with the development of economic and social variables such as GDP growth rate, per capita income and additional value of sub-sectors hotel,  its contribution should still further be improved. The targeting of hotel tax that has not been realistic is one of the cause factors. The revenue target shoud be based on the real potential or capacity but in fact it is only based on the estimation data (forecast), so it is not impossible if the realization of receipts by a ratio of more than 100% was seen not optimal.   This study aimed to calculate the real potential of hotel tax, the level of effectiveness : the tax effort and the capacity of the tax. Then through the system and procedures of the hotel tax collection, Pontianak city government will have an objective guideline in determining the target and if there is a gap between the realization and the target, strategies can be created to optimize the reception of the hotel tax.   The approach taken to answer the research purpose of this thesis was to determine the real potential of the hotel tax in year t, which was obtained by diverting tax rates with the overall turn over of the hotel. Meanwhile the level of effectiveness was directy estimated through the comparison between the proceeds of the revenue target and the real potential of hotel tax in order to obtain the ratio of the tax capacity and tax effort.   Based on the results of the count in this study, it can be seen that the total of the real potential of hotel tax in Pontianak in 2013 amounted  to USD 18.329.351.000,- with the average effectiveness level of the tax capacity 104,22%  per year (very effective), but the level of effectiveness of tax effort (tax-effort) amounted to 62.97% (less effective) so it still cannot boost the hotel tax revenue in the city of Pontianak.   The low tax-effort is due to: lack of technology utilization, weak control to the officers and business doers, and no strict sanctions against violations of hotel tax regulations. Therefore, in order to optimize the hotel tax revenue, targeting should be adjusted to the size of the potential. Keywords : Potential,Effectiveness, Effort and Capacity Taxes